2023
DOI: 10.1038/s41467-023-38456-y
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib overcomes glucocorticoid resistance in B-cell acute lymphoblastic leukemia

Abstract: Resistance to glucocorticoids (GC) is associated with an increased risk of relapse in B-cell progenitor acute lymphoblastic leukemia (BCP-ALL). Performing transcriptomic and single-cell proteomic studies in healthy B-cell progenitors, we herein identify coordination between the glucocorticoid receptor pathway with B-cell developmental pathways. Healthy pro-B cells most highly express the glucocorticoid receptor, and this developmental expression is conserved in primary BCP-ALL cells from patients at diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…To our knowledge, there are no clinical trials on pediatric populations specifically targeting the EPH/ephrin signaling pathway. However, as mentioned above, targeted agents are used off-label in mainly solid pediatric neoplasms (e.g., Dasatinib, Trametinib), and, moreover, novel therapies are used in the fields of clinical trials (e.g., Regorafenib in Ewing sarcoma) and multi-target tyrosine kinase (and nontyrosine kinase) receptors, including EPH/ephrin members [143][144][145]. Other therapeutic strategies that need to be tested in pediatric populations after presenting promising results in older patients are antibody-drug conjugates (e.g., anti-EphA3 antibody-drug conjugate, which has shown promising results in glioblastoma multiforme, EphB2 antibody-2H9, which has shown promising results in colorectal cancer) and small molecules targeting protein-protein interactions, specifically the polyphenol and steroidal derivatives, α1 agonist doxazosin, 2,5-dimethylpyrrol-1-yl-benzoic acids, and amino acid conjugates of lithocholic acid, which are potential tumor suppressors (e.g., resulting in EPHA2-mediated tumor suppression in prostate cancer cells) [146][147][148][149].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no clinical trials on pediatric populations specifically targeting the EPH/ephrin signaling pathway. However, as mentioned above, targeted agents are used off-label in mainly solid pediatric neoplasms (e.g., Dasatinib, Trametinib), and, moreover, novel therapies are used in the fields of clinical trials (e.g., Regorafenib in Ewing sarcoma) and multi-target tyrosine kinase (and nontyrosine kinase) receptors, including EPH/ephrin members [143][144][145]. Other therapeutic strategies that need to be tested in pediatric populations after presenting promising results in older patients are antibody-drug conjugates (e.g., anti-EphA3 antibody-drug conjugate, which has shown promising results in glioblastoma multiforme, EphB2 antibody-2H9, which has shown promising results in colorectal cancer) and small molecules targeting protein-protein interactions, specifically the polyphenol and steroidal derivatives, α1 agonist doxazosin, 2,5-dimethylpyrrol-1-yl-benzoic acids, and amino acid conjugates of lithocholic acid, which are potential tumor suppressors (e.g., resulting in EPHA2-mediated tumor suppression in prostate cancer cells) [146][147][148][149].…”
Section: Discussionmentioning
confidence: 99%
“… Indicated that the combination of GCs and TKIs may improve therapeutic outcomes in B-ALL patients. [ 128 ] AML scDNA-seq AML Patients treated with VEN-based therapy with higher response rates were associated with NPM1 or IDH2 mutations, and poor responses or relapse were associated with TP53 loss or kinase activation, particularly FLT3 activation. Provided insights for the risk stratification and prognostic prediction with older AML patients receiving venetoclax-based combination therapies.…”
Section: Single-cell Studies Provide Further Insights Into Drug Effec...mentioning
confidence: 99%
“…CD44, EPC1, SET2D, and SOCS2) [ 127 ]. Another recent study went deep into the mechanism of GC resistance and identified glucocorticoid receptor pathway was coordinated with the B-cell receptor (BCR) pathway in B-cell precursor acute lymphoblastic leukemia (BCP-ALL) [ 128 ]. By single-cell proteomics and RNA-seq, the authors identified that the BCR signaling pathway was enriched during GC treatment, with activation of BCR downstream pathway including the PI3K/mTOR and CREB signaling and accounted for GC resistance.…”
Section: Single-cell Studies Provide Further Insights Into Drug Effec...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some exemplary (relatively) recent applications of (squared) Mahalanobis distance can be found e.g. in Xu et al [301], Sun et al [302], Timmermann et al [303], Wauchope et al [304], Weinberger [305], Wen et al [306], Yang et al [307], Zhang et al [308], Burssens et al [309], Choi et al [310], Choi et al [311], Dahlin et al [312], Ebrahimi et al [313], Jeong et al [314], Kim et al [315], Nowakowski et al [316], Qu et al [317], Rabby et al [318], Sarno et al [319], Tang et al [320], Tsvieli & Weinberger [321], Zhang et al [322], Zhou et al [323]. Some exemplary (relatively) recent applications of generally non-separable (ordinary/classical) Bregman distances appear e.g.…”
Section: A Further Divergences and Friendsmentioning
confidence: 99%